Moscas-das-frutas (Diptera: Tephritidae) e seus Parasitóides (Hymenoptera: Braconidae), em Pomares Domésticos, nos Municípios de Apodi e Baraúna, Rio Grande do Norte - Costa, Gleider Maria de Menezes (Universidade Federal Rural do Semi-Árido, 2011)
Rio Grande do Norte State (RN) is one of the greatest producers of tropical fruits, for it has adequate edaphoclimatic conditions for the large scale development of such activity. Due to the negative impact that fruit flies represent to agribusiness, studies regarding this plague are necessary in regions with potential for fruit production. It is also crucial the knowledge on the existing region fruit parasites as to strategically plan the biological control and integrated handling of plagues. The present work was performed in the metropolitan areas of Apodi and Baraúna, located in the semiarid region of RN. It had as objectives identifying the fruit fly species, the distribution patterns and the relationships with their host plants and the associated parasitoids. After three years of data collection, 15.608 fruits and 9.961 tephritid were obtained, of which 4.953 samples of Anastrepha and 5.008 of Ceratitis capitata. The Anastrepha species present in individualized fruits were Anastrepha zenildae (35,82%), Anastrepha sororcula (8,19%), Anastrepha obliqua (4,45%), Anastrepha pickeli (0,74%) and C. capitata (50,8%). Considering the simultaneous presence of fruit flies and parasitoids of the same fruit, it was found Doryctobracon areolatus associated with A. obliqua in cajá fruits; in guavas, there was an association of the parasite with A. sororcula and A. zenildae; in juá fruits, the association was observed only with A. zenildae. The only parasitoid found was the D. areolatus. The total parasite rate found was 4%, valid only for Anastrepha, for it was not found an association of D. areolatus with C. capitata in a same fruit. The cajá host has presented a greater rate of natural parasitism (19%). The logistic regression analysis indicates that the fruit size does not influence the condition of being or not infested. The results of the simple linear regressions indicate that, in general, the fruit weight does not determine the number of puparium. The correlations between the climatic and the biotic factors only point that rainfall affects negatively the percentage of infected fruits
Fruit flies (Diptera: Tephritidae) and its Parasitoids (Hymenoptera: Braconidae), in Domestic Orchards, in Regions of Apodi e Baraúna, Rio Grande do Norte
Keywords: Parasitoid; Fruit infestation; Fruit growing; Semiarid; Moscas-das-frutas; Parasitóide; Infestação de frutos; Fruticultura; Semiárido; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA